Incidence of wound infection in common paediatric day care surgeries following a no-antibiotic protocol: a viable recommendation for a public hospital in India - Kekre, Geeta; Dikshit, Vishesh; Kothari, Paras; Mudkhedkar, Kedar; Gupta, Abhaya; Patil, Prashant (International Surgery Journal, 2018)
Background: The use of broad spectrum antibiotic administered intravenously 1 hour before incision has a well-established role in preventing surgical site infection following major surgeries. However, the benefit of this practice in clean, day care surgeries is less clear. The aim of the our study is to determine the incidence of wound infection in paediatric day care surgeries where antibiotics were not used. The objective of the present study was to observe the rate of Surgical Site Infection in paediatric day care surgery at a tertiary care public hospital where prophylactic antibiotics are not used empirically. Methods: We reviewed all paediatric patients undergoing day care common procedures namely herniotomy, open orchiopexy, circumcision and other minor procedures such as lymph node biopsy, lipoma excision, mucous retention cyst excision and dermoid cyst excision at our institute in a public hospital between January 2015 and December 2016. Those with heart diseases requiring infective endocarditis prophylaxis, those with immunosuppression and those who had received antibiotics perioperatively for any reason other than treatment of surgical site infection were excluded. Surgical site infection (SSI) was classified as superficial or deep as defined by the Centre For Disease Control (CDC). Results: A total of 576 paediatric patients underwent clean day- care procedures at our institute between January 2015 and December 2016, of which 478 patients met the inclusion criteria and were included in the study. 2 (0.41%) of these 478 patients developed surgical site infection. 1 patient had serous discharge at one point along the suture line while the other developed pus and required debridement. Conclusions: Clean day- care surgeries in children can be carried out safely without the empiric use of perioperative antibiotics even in the setting of a public hospital in a developing country.